Impact of Antenna Placement on Frequency Domain Adaptive Antenna Array in Hybrid FRF Cellular System - Sri Maldia Hari Asti; Wei Peng; Fumiyuki Adachi (International Journal of Antennas and Propagation)
Frequency domain adaptive antenna array (FDAAA) is an effective method to suppress interference caused by frequency selective fading and multiple-access interference (MAI) in single-carrier (SC) transmission. However, the performance of FDAAA receiver will be affected by the antenna placement parameters such as antenna separation and spread of angle of arrival (AOA). On the other hand, hybrid frequency reuse can be adopted in cellular system to improve the cellular capacity. However, optimal frequency reuse factor (FRF) depends on the channel propagation and transceiver scheme as well. In this paper, we analyze the impact of antenna separation and AOA spread on FDAAA receiver and optimize the cellular capacity by using hybrid FRF.